Synthesis, Characterization and Antibacterial Activity of Some Penicillin Derivatives - A. Jawad, Asmaa; J. Alabdali, Ammar (Al-Nahrain Journal of Science, 2020)
This study illustrated the synthesis of two new di amidine compounds ([c] and [d]) by reaction of 6-amino penicillanic acid (6-APA) with di α-amino nitrile compounds ([a] and [b]). [a] and [b] di α-amino nitrile compounds synthesized from the condensation reaction on aldehyd and di amine in the presence of potassium cyanid as one pot- three components reaction. The new di amidine compounds ([c] and [d]) have been proven their efficiency by inhibiting some types of bacteria (Staphylococcus aurous, Streptococcus, Escherichia coli and klebsiella). Amidine compound [d] showed better effect than [c] against the selected bacteria. The synthesized compounds were characterized by conventional techniques using infrared spectrophotometer (IR) and proton-nuclear magnetic resonance (1H-NMR).